Distinct Effects of the Cervicovaginal Microbiota and Herpes Simplex Type 2 Infection on Female Genital Tract Immunology. (13th February 2017) - Shannon, B.; Gajer, P.; Yi, T. J.; Ma, B.; Humphrys, M. S.; Thomas-Pavanel, J.; Chieza, L.; Janakiram, P.; Saunders, M.; Tharao, W.; Huibner, S.; Shahabi, K.; et al.
Summary: High-diversity vaginal microbiota was associated with inflammatory cytokines, while herpes simplex virus type-2 (HSV-2) infection correlated with CD4 + T-cell numbers and a distinct cytokine profile. This suggests that HSV-2 infection and the genital microbiota may influence human immunodeficiency virus susceptibility through independent biological mechanisms. Abstract: Background: Genital inflammation is a key determinant of human immunodeficiency virus (HIV) transmission, and may increase HIV-susceptible target cells and alter epithelial integrity. Several genital conditions that increase HIV risk are more prevalent in African, Caribbean, and other black (ACB) women, including bacterial vaginosis and herpes simplex virus type-2 (HSV-2) infection. Therefore, we assessed the impact of the genital microbiota on mucosal immunology in ACB women and microbiome-HSV-2 interactions. Methods: Cervicovaginal secretions and endocervical cells were collected by cytobrush and Instead Softcup, respectively. T cells and dendritic cells were assessed by flow cytometry, cytokines by multiplex enzyme-linked immunosorbent assay (ELISA), and the microbiota by 16S ribosomal ribonucleic acid gene sequencing. Results: The cervicovaginal microbiota of 51 participants were composed of community state types (CSTs) showing diversity (20/51; 39%) or predominated by Lactobacillus iners (22/51; 42%), L. crispatus (7/51; 14%), or L. gasseri (2/51; 4%). High-diversity CSTs and specific bacterial phyla ( Gardnerella vaginalis and Prevotella bivia ) were strongly associated with cervicovaginal inflammatory cytokines, but not with altered endocervical immune cells. However, cervical CD4 + T-cell number was associated with HSV-2 infection and a distinct cytokine profile. Conclusions: This suggests that the genital microbiota and HSV-2 infection may influence HIV susceptibility through independent biological mechanisms.